α-Diimine Ni-Catalyzed Ethylene Polymerizations: On the Role of Nickel(I) Intermediates - Igor E. Soshnikov (MDPI AG, 2021)
Nickel(II) complexes with bidentate N,N-α-diimine ligands constitute a broad class of promising catalysts for the synthesis of branched polyethylenes via ethylene homopolymerization. Despite extensive studies devoted to the rational design of new Ni(II) α-diimines with desired catalytic properties, the polymerization mechanism has not been fully rationalized. In contrast to the well-characterized cationic Ni(II) active sites of ethylene polymerization and their precursors, the structure and role of Ni(I) species in the polymerization process continues to be a “black box”. This perspective discusses recent advances in the understanding of the nature and role of monovalent nickel complexes formed in Ni(II) α-diimine-based ethylene polymerization catalyst systems.